Further Astrochemical Insights From Bond Strengths of Small Molecules Containing Atoms From the First Three Rows of the Periodic Table - Doerksen, Edmund S.; Fortenberry, Ryan C. (Frontiers in Astronomy and Space Sciences, 2021)
The atoms contributing to the strongest "single bonds" on the periodic table do not continue to produce the strongest "double bonds" or "triple bonds." In fact, the opposite appears to be the case. This quantum chemical examination of nominal X=Y and X≡Y bonds in model molecules of atoms from the first three rows of the periodic table shows that the strongest "double bond" is in formaldehyde once the astrophysically-depleted Be and B atoms are removed from consideration. The strongest "triple bond" is a close match between acetylene and N2. However, these results indicate that astrophysical regions containing a high abundance of hydride species will likely be areas where inorganic oxide formation is favored. Those where H2 molecules have already been dissociated will favor organic/volatile astrochemistry.